The role of the school principal in professional development from the point of view of intermediate science and mathematics teachers in Riyadh - Al Abdulsalam, May Abdulaziz; Kaaki, Saham Mohammed (Journal of Educational and Psychological Sciences, 2025)
The aim of this study was to explore the role of school principals in professional development from the perspective of middle school science and mathematics teachers in Riyadh. The researcher employed a descriptive-analytical approach and used a questionnaire to collect data from a randomly selected sample consisting of 38 science teachers and 42 mathematics teachers. The results revealed that the mechanisms for enhancing the quality of professional development, from the teachers’ perspective, were rated highly with a mean score of 2.33 out of 3. The principal’s attention to key professional development tasks related to motivation, decision-making, evaluation, communication skills, and teaching skills received a moderate rating with a mean of 2.07. Similarly, professional development domains related to research, training, and the use of educational technology also received a moderate rating, with a mean of 1.97. The most significant obstacles to professional development were the burden of additional work responsibilities and teacher absenteeism, with a mean score of 2.10, indicating a high level of impact. The findings also showed no statistically significant differences at the (α ≤ 0.05) level in the role of the school principal in professional development based on the interaction between age and experience. Based on these findings, the researchers recommended empowering principals professionally, motivating teachers, enhancing their skills, promoting participatory decision-making, encouraging experience exchange, supporting field-based educational research, and conducting further studies on the topic.
Keywords: Science teachers; Professional development; School principals; Mathematics teachers; middle stage; Saudi Arabia